Digital Transformation of BMT Sunan Drajat Through Sharia Fintech in the Perspective of Maqasid Al-Shariah - Nur Zahrotul Laily; Nafidatun Nikmah; Akhmad Sirojudin Munir (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2026)
Background – The rapid development of financial technology has driven Islamic financial institutions to adopt digital systems while maintaining compliance with Maqasid al-Shariah. However, studies evaluating Sharia fintech from a Maqasid perspective remain limited. Aim – This study analyzes the digital transformation of BMT Sunan Drajat Lamongan through Sharia fintech based on Maqasid al-Shariah. Design / methodology / approach – A qualitative approach was employed using interviews, observation, and documentation, analyzed through the Miles and Huberman interactive model. Findings – The results show that BMT Sunan Drajat has successfully integrated Sharia fintech with Maqasid al-Shariah. Hifz al-mal is implemented through real asset–based fund management, hifz al-din through strict Sharia compliance, and social welfare (maslahah) through community empowerment and accessible microfinancing. Digital services enhance financial inclusion, transparency, and operational efficiency. However, challenges remain in limited digital adoption among elderly members and infrastructure constraints. Conclusion – The digital transformation of BMT Sunan Drajat aligns with Maqasid al-Shariah and supports sustainable financial inclusion and social welfare. Research implication – The study provides practical recommendations for Islamic microfinance institutions to strengthen asset-based financing, digital transparency, and financial literacy while enhancing regulatory support and technological capacity. Limitations – The study is limited by the number of informants and the relatively low usage of digital services among members.